Global Trends in Orthopedic Biofilm Research: A Bibliometric Analysis of 1994-2022 - Hu Z; Yin X; Fan G; Liao X (Journal of Multidisciplinary Healthcare, 2024)
Zhouyang Hu,1,2,* Xiaobing Yin,3,* Guoxin Fan,1,2 Xiang Liao1,2 1Department of Pain Medicine, Huazhong University of Science and Technology Union Shenzhen Hospital, Shenzhen, People’s Republic of China; 2Guangdong Key Laboratory for Biomedical Measurements and Ultrasound Imaging, National-Regional Key Technology Engineering Laboratory for Medical Ultrasound, School of Biomedical Engineering, Shenzhen University Medical School, Shenzhen, 518060, People’s Republic of China; 3Nursing Department, Shanghai Tenth People’s Hospital, Tongji University School of Medicine, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Guoxin Fan; Xiang Liao, Department of Pain Medicine, Huazhong University of Science and Technology Union Shenzhen Hospital, Shenzhen, People’s Republic of China, Tel +86-18529093630 ; +86-13725595056, Email fan06309@163.com; liaoxiang75@email.szu.edu.cnObjective: Bibliometric analysis is commonly used to visualize the knowledge foundation, trends, and patterns in a specific scientific field by performing a quantitative evaluation of the relevant literature. The purpose of this study was to perform a bibliometric analysis of recent studies in the field of orthopedic biofilm research and identify its current trends and hotspots.Methods: Research studies were retrieved from the Web of Science Core Collection and Scopus databases and analyzed in bibliometrix with R package (4.2.2).Results: A total of 2426 literature were included in the study. Journal of orthopaedic research and Clinical orthopaedics and related research ranked first in terms of productivity and impact, with 57 published articles and 32 h-index, respectively. Trampuz A, Ohio State Univ and the United States ranked as the most productive authors, institutions, and countries. Biofilm formation, role of sonication, biomaterial mechanism and antibiotic loading have been investigated as the trend and hotspots in the field of orthopedic biofilm research.Conclusion: This study provides a thorough overview of the state of the art of current orthopedic biofilm research and offers valuable insights into recent trends and hotspots in this field.Keywords: biofilm, orthopedic infection, bibliometric analysis, hotspot, research trend